The challenges among Small Medium Enterprise (SME) contractors towards BIM adoption in Malaysia / Irfan Arshad and Farhan Md Dahlan - Arshad, Irfan; Md Dahlan, Farhan (2023)
Building Information Modelling (BIM) drives construction stakeholders to increase productivity and efficiency. The implementation of BIM has met the requirements during the design phase but is lacking in the construction phase. The purpose of this paper is to identify and understand the challenges of BIM adoption among Small Medium Enterprise (SME) contractors in Malaysia. A questionnaire survey was carried out among G4 contractors throughout Kuala Lumpur to ascertain and analyse the challenges of BIM adoption. The results derived from descriptive analysis suggested two significant underlying challenges: companies need to spend money on employee training to adapt to the use of new technology and the culture of the construction industry. Identifying the factors provides more information regarding the challenges among G4 contractors towards BIM adoption in Malaysia. It is hoped that the result could assist industry players in improving BIM adoption in Malaysia.